2014
DOI: 10.4037/ajcc2014860
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Training for Nurses in Sterile Techniques During Central Vein Catheterization

Abstract: Background The effectiveness of simulation-based training of critical care nurses in sterile techniques has not been determined. Objective To evaluate the effectiveness of simulation-based training of critical care nurses to use sterile techniques during central vein catheterization and the effect of such training on infection rates. Methods A prospective controlled study with 12-month observational follow-up to assess the rate of catheter-related bloodstream infections in a 23-bed medical, surgical, neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…Evaluation of the evidence from 15 studies (five interrupted case series [25][26][27][28][29], five qualitative [24,[30][31][32][33], two controlled before-after [34,35], two non-controlled before-after [36,37], and one mixed methods [38]) showed that IPC education that involves frontline health care workers in a practical, hands-on approach and incorporates individual experiences is associated with decreased HAI and increased hand hygiene compliance. Twelve studies were from high-income countries [24-28, 31-34, 36-38], two from one upper-middleincome country [29,35], and one from a LMIC [30].…”
Section: (Strong Recommendation Moderate Quality Of Evidence)mentioning
confidence: 99%
“…Evaluation of the evidence from 15 studies (five interrupted case series [25][26][27][28][29], five qualitative [24,[30][31][32][33], two controlled before-after [34,35], two non-controlled before-after [36,37], and one mixed methods [38]) showed that IPC education that involves frontline health care workers in a practical, hands-on approach and incorporates individual experiences is associated with decreased HAI and increased hand hygiene compliance. Twelve studies were from high-income countries [24-28, 31-34, 36-38], two from one upper-middleincome country [29,35], and one from a LMIC [30].…”
Section: (Strong Recommendation Moderate Quality Of Evidence)mentioning
confidence: 99%
“…Reporting format of experience levels was disparate. Eight studies included samples of nurses with varying experience levels, ranging from <1 year to over 25 years of experience (Ballangrud, Hall‐Lord, Hedelin, & Persenius, ; Gerolemou et al, ; Kim, ; Klipfel et al, ; Liaw et al, ; Pati, Cason, Harvey, Evans, & Erwin, ; Trbovich, Pinkney, Cafazzo, & Easty, ; Wilson et al, ). One study was limited to inexperienced or entry‐level nurses with <2 years of experience (Roots, Thomas, Jaye, & Birns, ).…”
Section: Resultsmentioning
confidence: 99%
“…The study designs of the included research studies were pilot studies (Roots et al, ; Wilson et al, ), quasi‐experimental study designs with either a one group pretest posttest design (Ballangrud et al, ; Braddock et al, ; Gerolemou et al, ; Klipfel et al, ; Liaw et al, ) or a nonrandom assignment to groups (Kim, ; Nevo et al, ; Pati et al, ; Raurell‐Torreada et al, ; Trbovich et al, ). Sample sizes ranged from N = 6 to 247 RNs, and the mean sample size was N = 70 RNs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Gerolemou et al (2014), the ability of the nurse to apply sterile techniques in the central ven catheterization procedure was evaluated. Six basic elements were used for the catheterization criteria and the skills of the students were evaluated.…”
Section: Introductionmentioning
confidence: 99%